Role of microglia in diabetic neuropathic pain - Wang, Qian; Xie, Yilin; Ma, Shichao; Luo, Hongliang; Qiu, Yue (Frontiers in Cell and Developmental Biology, 2024)
Approximately one-third of the patients with diabetes worldwide suffer from neuropathic pain, mainly categorized by spontaneous and stimulus-induced pain. Microglia are a class of immune effector cells residing in the central nervous system and play a pivotal role in diabetic neuropathic pain (DNP). Microglia specifically respond to hyperglycemia along with inflammatory cytokines and adenosine triphosphate produced during hyperglycemic damage to nerve fibers. Because of the presence of multiple receptors on the microglial surface, microglia are dynamically and highly responsive to their immediate environment.Following peripheral sensitization caused by hyperglycemia, microglia are affected by the cascade of inflammatory factors and other substances and respond accordingly, resulting in a change in their functional state for DNP pathogenesis. Inhibition of receptors such as P2X reporters, reducing cytokine expression levels in the microglial reactivity mechanisms, and inhibiting their intracellular signaling pathways can effectively alleviate DNP. A variety of drugs attenuate DNP by inhibiting the aforementioned processes induced by microglial reactivity. In this review, we summarize the pathological mechanisms by which microglia promote and maintain DNP, the drugs and therapeutic techniques available, and the latest advances in this field.